Feasibility of 'parkrun' for people with knee osteoarthritis: A mixed methods pilot study. Issue 2 (June 2022) - Sutton, L.P.; Lahham, A.; Jose, K.; Moore, M.N.; Antony, B.; Grunseit, A.; Cleland, V.; Balogun, S.; Winzenberg, T.; Jones, G.; Aitken, D.
Abstract: Objective: To investigate the feasibility of 'parkrun' for people with knee osteoarthritis (OA) and examine its potential to improve symptoms and increase physical activity. Design: This uncontrolled mixed methods pilot study enrolled people with knee OA not meeting physical activity guidelines. Participants were asked to walk in four consecutive parkrun events supervised by an exercise physiologist/physiotherapist. Feasibility was assessed by recruitment data (numbers screened and time to enrol 15 participants), adherence to the protocol, acceptability (measured by confidence, enjoyment, difficulty ratings and qualitative interviews), and safety (adverse events). Secondary measures were changes in knee pain, function, stiffness, and physical activity levels. Results: Participants (n ​= ​17) were enrolled over 11 months and recruitment was slower than anticipated. Fourteen participants attended all four parkruns and three of these participants shortened the 5 ​km course to ∼3 ​km. Across all four parkruns, 75% of participants reported high confidence that they could complete the upcoming parkrun and the majority (87%) enjoyed participating. Most participants rated parkrun either "slightly difficult" (38.5%) or "moderately difficult" (35%) and two mild adverse events were reported. Participants showed improvements in knee pain, function, stiffness, and physical activity levels. Conclusions: This pilot study demonstrates parkrun's feasibility, acceptability, safety and, its potential to improve knee OA symptoms and physical activity levels. Participating in parkrun was acceptable and enjoyable for some, but not all participants. The scalability, accessibility and wide appeal of parkrun supports the development of larger programs of research to evaluate the use of parkrun for people with knee OA.